P542 Short term efficacy, safety and thromboembolic risk of tofacitinib in moderate to severe Ulcerative Colitis. (30th January 2023) - Cingolani, L; Barberio, B; Zelante, A; Ribaldone, D; Testa, G; Bertani, L; Buda, A; Zingone, F; Savarino, E V
Abstract: Background: Tofacitinib is a small oral molecule approved to treat moderate to severe ulcerative colitis (UC), which effectiveness and safety is still poorly known in UC patients. Recent concerns have been raised regarding its administration at high dosage in UC patients because of a likely higher incidence of drug-related thromboembolic events. Methods: The aim of this study was to evaluate short-term effectiveness and safety of tofacitinib. As secondary aim, we analyzed the state of blood coagulation at baseline in order to evaluate whether it could predict thromboembolic events in relation to demographic, clinical and biochemical characteristics. A multicenter, retrospective, observational study was conducted, including patients from March 2021 to October 2022; a prospective single-centre sub-study concerning the thromboembolic risk was performed. At baseline, demographic, clinical, biochemical and endoscopic data, and previous therapies were recorded; quality of life was evaluated through IBD-Disability Index (IBD-DI) and Pittsburgh Sleep Quality Index (PSQI). In a subgroup of patients, a thrombophilic screening and a Rotational Thromboelastometry (ROTEM) were performed at baseline. Patients were reassessed after 8 weeks, 6 months and 1 year, evaluating for each timepoint clinical and biochemical characteristics, IBD-DI and PSQI, and reporting adverse events (AEs) and discontinuation of therapy. The following clinical outcomes were considered: benefit, steroid-free remission and response. Results: 44 adult patients were enrolled. The overall clinical benefit was 54.2%, summing up 45.8% of subjects in steroid-free clinical remission and 8.3% with clinical response; significant short-term improvement of IBD-DI and PSQI scores (p=0.000 in both cases after 6 months of therapy) was observed. Patients previously treated with less than two different biological therapies had major rates of clinical benefit at 6 months (p=0.045). Ten AEs, including one venous thrombosis, were reported; global therapy failure rate was 31.4%. In the subgroup with additional data on coagulation (17 patients), we did not observe significant alterations of coagulating factors or inhibitors, nor of ROTEM parameters, although some coagulation features were significantly increased in obese patients (FII, p=0.030; FIX, p=0.000; FX, p=0.000; fibrinogen blood levels, p=0.030) and subjects older than 40 years old (FVIII, p=0.020). We did not find significant correlation with gender, smoking habit, concomitant steroid therapy, CRP, fecal calprotectin. Conclusion: Our data confirm literature ones on effectiveness and safety of tofacitinib in UC patients, while the risk of thrombosis needs to be better evaluated in larger longitudinal studies.